THE IMPACT OF MANUAL THERAPY TECHNIQUES ON PAIN, DISABILITY AND IL-1B LEVELS IN PATIENTS WITH CHRONIC CERVICAL PAIN (International Journal of Physiotherapy, 2019)
Background: Chronic neck pain is a common musculoskeletal dysfunction, and Manual Therapy is one of the effective treatment modalities, but underlying mechanisms of action are unclear. The study's purpose was to investigate the short-term effect of mobilization-manipulations on patient’s symptoms and to detect changes in the concentration of inflammatory biomarker interleukin-1b.Methods: Twenty-two patients aged 20-50 years with chronic neck pain, randomly assigned into two groups. The study group received nine sessions of a three-week Manual Therapy intervention. The control group received SHAM Manual Therapy of the same dosage. Pain and functionality measures conducted before and after the intervention via NPRS and NDI scales, respectively. Blood samples collected at baseline, after the first session and post-intervention, detecting IL-1β concentration, using the corresponding ELISA kit. Mixed ANOVA statistical analysis implemented for differences in the GROUP-TIME factors.Results: There was a significant statistical interaction between factors and significant main effects on pain, functionality, and IL-1β (p